The administrative and organizational institutions of the castle of Bani Abbas under the Ottoman rule Algeria (1510 -1830 A.D.) - Boudrouaz, Abdelhamid; Bouzid, Fouad (The Algerian Historical Journal, 2026)
The castle of Bani Abbas was the last empire in the Middle Maghreb (Algeria), where the family of Sheikh Abderrahmane, whose son Abbas had a role in the emergence of this Empire under the events of unrest political conditions, coincided with the Spanish attacks on the coast of Algeria with the Barbaros brothers; there was a kind of relationship of reconciliation and conflict between the princes of the castle and the Ottoman authority in Algeria, until the fall of the emirate in the hands of The Ottoman Empire in Algeria at the end of the reign of Si Nasser in 1604 A.D.and the transfer of the seat of the government to Medjana (Mjana) to represent the castle a traditional customary system represented in the Amazigh custom system, embodied in the village council (Thagamath) (Thajmaath).